Co(ii)Tetraphenyltetraphenanthroporphyrin@MWCNTs: enhanced π–π interaction for robust electrochemical catalysis. (19th June 2019) - Gu, Tingting; Tao, Jiayu; Zhu, Weihua; Mack, John; Soy, Rodah C.; Nyokong, Tebello; Xu, Haijun; Li, Minzhi; Liang, Xu
Abstract : A cobalt(ii )tetraphenyltetraphenanthroporphyrin with phenanthrene-fused pyrrole rings was applied for robust HER and ORR. Abstract : Herein, a cobalt(ii ) tetraphenyltetraphenanthroporphyrin (Co(ii )TPTPP) with phenanthrene-fused pyrrole rings was synthesized and characterized. Moreover, a detailed analysis of its optical and redox properties was carried out by comparing the results obtained via optical spectroscopy and electrochemistry with the trends predicted via a series of DFT and TD-DFT calculations. The electrochemistry results demonstrated that the π-expanded Co(ii )TPTPP interacted strongly with multiwall carbon nanotubes (MWCNTs), which were finally immobilized on carbon nanotubes via noncovalent interactions and further deposited on glassy carbon. This strong immobilization via π–π stacking between Co(ii )TPTPP and MWCNTs leads to significantly stable electrochemically catalyzed hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR), which provides a new insight into the understanding electron transfer channels.